NOROVIRUS INFECTION (SYSTEMATIC REVIEW) - N. I. Khokhlova; D. V. Kapustin; E. I. Krasnova; I. Ya. I.Yа. Izvekova (Журнал инфектологии)
The share of norovirus infection is 17–20% of all cases of acute gastroenteritis in the world. The dominant II genogroup of noroviruses is characterized by rapid variability. The new recombinant norovirus GII.P16-GII.2 caused a sharp increase in the incidence of gastroenteritis in Asian and European countries during the winter season 2016–2017. The epidemiological features of norovirus infection are long-term excretion of the pathogen from the body of patients and carriers of viruses, especially in persons with immunosuppression; the implementation of various transmission routes (food, water, contact, aerosol), high contagiosity, winter seasonality in the countries of the northern hemisphere. In recent years, two human systems for the cultivation of noroviruses in vitro have been created, a double tropism of noroviruses has been established for immune cells and epithelial cells of the intestine, and the life cycle of noroviruses has been studied. The microbiota and its members can be either protective or stimulating for norovirus infection. Lactobacillus may play a protective role against norovirus infection. The existence of chronic norovirus infection lasting from several months to several years is proved, especially in patients with immunodeficiency. Severe form of norovirus infection and deaths are more often recorded in young children, the elderly, patients with comorbidity and immunocompromised individuals. The clinical picture of norovirus gastroenteritis is similar in many respects to other viral gastroenteritis, which determines the need for laboratory verification of the diagnosis. The polymerase chain reaction method with reverse transcription is the most widely used in the world for diagnosing infection in patients and for detecting the virus in food and environmental objects. There are still no approved vaccines and antiviral drugs against this infection. Recommended therapeutic interventions include, along with rehydration with hypoosmolar solutions, the administration of specific probiotics such as Lactobacillus GG or Saccharomyces boulardii, diosmectit and racecadotril.